2000
DOI: 10.1002/cd.23220008706
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing interpersonal relationships in the cultural contexts of individualism and collectivism

Abstract: The expressed values of European American and Latino children, their parents, and their teachers reveal the multifaceted nature of individualistic and collectivistic conceptions of relationships and the varied ways in which cultural value conflict may be manqested in children's daily developmental settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 6 publications
(7 reference statements)
3
69
0
4
Order By: Relevance
“…Research by Raeff, Greenfield, and Quiroz (2000) demonstrated that immigrant Latino families solved home-school problem scenarios in ways very different from their child's fifth-grade teacher and their own children, to some extent. The collectivistic families tended to value helping and sharing more than personal choice and individual autonomy.…”
Section: Research On Individualism-collectivism With Elementary Schoomentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Raeff, Greenfield, and Quiroz (2000) demonstrated that immigrant Latino families solved home-school problem scenarios in ways very different from their child's fifth-grade teacher and their own children, to some extent. The collectivistic families tended to value helping and sharing more than personal choice and individual autonomy.…”
Section: Research On Individualism-collectivism With Elementary Schoomentioning
confidence: 99%
“…Phase I consisted of three half-day videotaped workshops presented over a period of four months. The workshops included administration of scenarios of home-school conflict (see Raeff et al, 2000) as a pretest to determine the teachers' orientation to problem solving based on individualistic or collectivistic perspectives (the pretest and posttest data were coded by the same team member who had established inter-rater reliability on the empirical study using the same scenarios), learning about the framework of individualism and collectivism, elicitation of teachers' examples of individualism-collectivism in their own classrooms, and teachers' sharing of the changes they made in their classrooms as a result of their new understanding of culture in terms of the individualism-collectivism framework. At the end of the third workshop, teachers responded to an alternate set of scenarios.…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking a somewhat different approach, Raeff, Greenfield, and Quiroz (2000) have argued that both individualism and collectivism are complex and multifaceted value systems. In spite of being complex, however, these systems are still useful for understanding different cultural values about relationships.…”
Section: Parental Ethnotheories In the United States: Independence/ Imentioning
confidence: 99%
“…집단 내 조화 를 중시하는 경향은 팀에 대한 몰입의 정도는 물론 암 묵적 이해(implicit understandings)의 정도를 높이고 [5] 팀 구성원들이 친밀한 관계를 유지하도록 한다 [10]. 이 처럼 사회적 관계에 대한 깊은 소속감을 인식할 때 구 성원들은 상호작용을 통한 활력을 느끼게 된다 [11].…”
unclassified